2021
DOI: 10.1021/acs.jpcc.1c07064
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic, Nonthermal Lattice Disordering Observed in Photoexcited PbS Quantum Dots

Abstract: Given their nanoscale dimensions, colloidal semiconductor nanocrystals provide unique systems for investigating the dynamics controlling surface chemistry and fundamental issues regarding lattice reorganization upon changes in electron distribution. These systems are particularly amenable to ultrafast electron probes, offering an atomic level picture of the lattice reorganization involved following photoexcitation. Here, we study lead sulfide (PbS) quantum dots with ultrafast electron diffraction to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 85 publications
(155 reference statements)
0
13
0
Order By: Relevance
“…Importantly, ln true( I I 0 true) vs the square of scattering vector s 2 displays a linear dependency (Figure d), which indicates that these changes in diffraction patterns arise mainly from the thermal effect of ultrafast lattice heating (see also Figure S5), namely the Debye–Waller (D–W) effect, apart from other possible photoinduced nonthermal effects. , This observation is consistent with that the lattice temperature deduced from the peak intensity change agrees very well with the value extracted from the peak position shift (Figures S6 and S7). In previous studies, an anomalous feature of the (400) Bragg peak in core/shell and PbS QDs within tens of picoseconds was observed and attributed to the hot carriers captured by the surface trap states. But no such feature was detected in our study because our pump photon energy is lower than the energy threshold (800 nm vs 400 nm) for such dynamical trapping .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, ln true( I I 0 true) vs the square of scattering vector s 2 displays a linear dependency (Figure d), which indicates that these changes in diffraction patterns arise mainly from the thermal effect of ultrafast lattice heating (see also Figure S5), namely the Debye–Waller (D–W) effect, apart from other possible photoinduced nonthermal effects. , This observation is consistent with that the lattice temperature deduced from the peak intensity change agrees very well with the value extracted from the peak position shift (Figures S6 and S7). In previous studies, an anomalous feature of the (400) Bragg peak in core/shell and PbS QDs within tens of picoseconds was observed and attributed to the hot carriers captured by the surface trap states. But no such feature was detected in our study because our pump photon energy is lower than the energy threshold (800 nm vs 400 nm) for such dynamical trapping .…”
mentioning
confidence: 93%
“…But no such feature was detected in our study because our pump photon energy is lower than the energy threshold (800 nm vs 400 nm) for such dynamical trapping . Also, surface passivation by chlorine quenches the dynamic surface trapping …”
mentioning
confidence: 99%
“…In this view, the observed photon energy may significantly underestimate the underlying energetic difference between the ground and excited electronic states . Further, the breadth of the trap emission would overwhelmingly arise from dynamical processes, so the effect of ensemble heterogeneity would be small. , Consensus remains to be found, and very recent reports emphasize the additional role of structural dynamism. ,,, Indeed, drawing on previous demonstrations, ,, we regard many spectroscopic observables as an ensemble- and time-average over the distribution of instantaneous configurations in size, shape, and surface within the ensemble . For instance, time-resolved measurements on core-only CdSe NCs have revealed that only a minority of NCs within the ensemble at a given instant undergo straightforward, monoexponential, radiative decay from band-edge states. , Instead, measurements on various CdSe nanostructures show partial suppression of prompt band-edge emission on single-picosecond time scales, consistent with pervasive but nonuniform hole trapping to states associated with the NC surface. ,, The key role of traps is supported by high-sensitivity transient fluorescence studies that observe substantial “delayed” PL consistent with a mixture of direct trap emission as well as the repopulation of band-edge states over widely distributed time scales. , Thus, it remains an open question whether sequential or correlated mechanisms for TET dominate when the photoexcited hole is rapidly trapped in a surface state. , …”
mentioning
confidence: 96%
“…37,40 Consensus remains to be found, and very recent reports emphasize the additional role of structural dynamism. 13,33,37,41 Indeed, drawing on previous demonstrations, 13,42,43 we regard many spectroscopic observables as an ensemble-and time-average over the distribution of instantaneous configurations in size, shape, and surface within the ensemble. 43 For instance, time-resolved measurements on core-only CdSe NCs have revealed that only a minority of NCs within the ensemble at a given instant undergo straightforward, monoexponential, radiative decay from band-edge states.…”
mentioning
confidence: 99%
See 1 more Smart Citation